Coatless alginate pellets as delayed-release drug carrier for inflammatory bowel disease treatment / Siti Hajar Md. Ramli - Md. Ramli, Siti Hajar (2016)
Conventional alginate pellets underwent rapid drug dissolution and failed to exert colon targeting unless subjected to complex coating. This study designed coatless delayed-release oral colon-specific alginate pellets for ulcerative colitis treatment. Alginate pellets, formulated with water-insoluble ethylcellulose and various calcium salts, were prepared using solvent-free melt pelletization technique which prevented reaction between processing materials during agglomeration and allowed such reaction to occur only in dissolution. Combination of acid-soluble calcium carbonate and highly water-soluble calcium acetate did not impart colon-specific characteristics to pellets due to pore formation in fragmented matrices. Combination of moderately water-soluble calcium phosphate and calcium acetate delayed drug release due to rapid alginate crosslinking by soluble calcium from acetate salt followed by sustaining alginate crosslinking by calcium phosphate. The use of 1:3 ethylcellulose-to-alginate enhanced the sustained drug release attribute. The ethylcellulose was able to maintain the pellet integrity without calcium acetate. Using hydrophobic prednisolone as therapeutic, hydrophilic alginate pellets formulated with hydrophobic ethylcellulose and moderately polar calcium phosphate exhibited colon-specific in vitro drug release and in vivo anti-inflammatory action. Coatless oral colon-specific alginate pellets can be designed through optimal formulation with melt pelletization as the processing technology.